Dynamics of diurnal cortisol and alpha-amylase secretion and their associations with PTSD onset in recent interpersonal trauma survivors. Issue 6 (12th April 2023) - Kinney, Kerry L.; Rao, Uma; Bailey, Brooklynn; Hellman, Natalie; Kelly, Chris; McAfee, Nicholas W.; Morris, Matthew C.
Abstract: Background: Dysfunction in major stress response systems during the acute aftermath of trauma may contribute to risk for developing posttraumatic stress disorder (PTSD). The current study investigated how PTSD diagnosis and symptom severity, depressive symptoms, and childhood trauma uniquely relate to diurnal neuroendocrine secretion (cortisol and alpha-amylase rhythms) in women who recently experienced interpersonal trauma compared to non-traumatized controls (NTCs). Method: Using a longitudinal design, we examined diurnal cortisol and alpha-amylase rhythms in 98 young women ( n = 57 exposed to recent interpersonal trauma, n = 41 NTCs). Participants provided saliva samples and completed symptom measures at baseline and 1-, 3-, and 6-month follow-up. Results: Multilevel models (MLMs) revealed lower waking cortisol predicted the development of PTSD in trauma survivors and distinguished at-risk women from NTCs. Women with greater childhood trauma exposure exhibited flatter diurnal cortisol slopes. Among trauma-exposed individuals, lower waking cortisol levels were associated with higher concurrent PTSD symptom severity. Regarding alpha-amylase, MLMs revealed women with greater childhood trauma exposure exhibited higher waking alpha-amylase and slower diurnal alpha-amylase increase. Conclusions: Results suggest lower waking cortisol in the acute aftermath of trauma may be implicated in PTSD onset and maintenance. Findings also suggest childhood trauma may predict a different pattern of dysfunction in stress response systems following subsequent trauma exposure than the stress system dynamics associated with PTSD risk; childhood trauma appears to be associated with flattened diurnal cortisol and alpha-amylase slopes, as well as higher waking alpha-amylase.